Analysis of The Use of No and Wa Particles In The Speech Translation of The Top 8 Miss International 2017 - Aurelia Richel Arrifah R (KIRYOKU, 2023)
Social media gives a lot of impacts. A lot of things are happening these days. Beauty pageants are popular in several realms of society and certain languages are being used in pageantries. Japanese is one of a language that is being used in pageantry called “Miss International”. Also, a quiet of phenomenons occurs when it comes to the use of Japanese particles. This study aims to reveal the use and meanings of No and Wa particles in the speech translation of the top 8 Miss International 2017 using the free translation method by J. C. Catford. The data source comes from the speech and translation of the top 8 contestants in Miss International 2017. Based on the results, it can be concluded that No and Wa particles are used to refer to something, as a particle of a word or grammar, or as an auxiliary of two or few words in Japanese. Most of the use of the No and Wa particles does not make a shift in meaning, only in a few sentences it happened.